STRATEGI BERTAHAN HIDUP MASYARAKAT NELAYAN MELALUI JARINGAN SOSIAL DI DESA CIKOANG, KABUPATEN TAKALAR - Saifuddin Saifuddin; Arisnawawi Arisnawawi (Universitas Negeri Makassar, 2023)
AbstractIndonesia consists of tens of thousands of islands and is known as a maritime country that has a very wide sea territory and enormous marine wealth. However, the living conditions of fishermen are generally relatively poor. In such conditions, social networks are very helpful as a strategy for fishermen to survive. This study aims to look at social networks in fishing communities in Cikoang Village, Takalar Regency. The method used is the mix method, namely a combination of methods by combining qualitative and quantitative analysis. This study found that the social network of fishing communities is divided into internal and external social networks. The internal social network of fellow fishermen, close family and neighbors is the social capital that is often used by the fishing community of Cikoang village in a survival strategy. Some fishermen use external social networks in survival strategies such as assistance from distant relatives who are migrating. Fishermen's external social network is not as strong as fishermen's internal social network. Fishermen who have families who are also neighbors are the most strategic social network for survival in the Cikoang Fishermen's Community, Takalar.